Characteristics and sources of submicron aerosols above the urban canopy (260 m) in Beijing, China, during the 2014 APEC summit - C. Chen; Y. L. Sun; W. Q. Xu; W. Du; L. B. Zhou; T. T. Han; Q. Q. Wang; P. Q. Fu; Z. F. Wang; Z. Q. Gao; Q. Zhang; D. R. Worsnop (Atmospheric Chemistry and Physics, 2015)
The megacity of Beijing has experienced frequent severe fine particle pollution during the last decade. Although the sources and formation mechanisms of aerosol particles have been extensively investigated on the basis of ground measurements, real-time characterization of aerosol particle composition and sources above the urban canopy in Beijing is rare. In this study, we conducted real-time measurements of non-refractory submicron aerosol (NR-PM1) composition at 260 m at the Beijing 325 m meteorological tower (BMT) from 10 October to 12 November 2014, by using an aerosol chemical speciation monitor (ACSM) along with synchronous measurements of size-resolved NR-PM1 composition near ground level using a high-resolution time-of-flight aerosol mass spectrometer (HR–ToF–AMS). The NR-PM1 composition above the urban canopy was dominated by organics (46 %), followed by nitrate (27 %) and sulfate (13 %). The high contribution of nitrate and high NO3− / SO42− mass ratios illustrates an important role of nitrate in particulate matter (PM) pollution during the study period. The organic aerosol (OA) was mainly composed of secondary OA (SOA), accounting for 61 % on an average. Different from that measured at the ground site, primary OA (POA) correlated moderately with SOA, likely suggesting a high contribution from regional transport above the urban canopy. The Asia–Pacific Economic Cooperation (APEC) summit with strict emission controls provides a unique opportunity to study the impacts of emission controls on aerosol chemistry. All aerosol species were shown to have significant decreases of 40–80 % during APEC from those measured before APEC, suggesting that emission controls over regional scales substantially reduced PM levels. However, the bulk aerosol composition was relatively similar before and during APEC as a result of synergetic controls of aerosol precursors. In addition to emission controls, the routine circulations of mountain–valley breezes were also found to play an important role in alleviating PM levels and achieving the "APEC blue" effect. The evolution of vertical differences between 260 m and the ground level was also investigated. Our results show complex vertical differences during the formation and evolution of severe haze episodes that are closely related to aerosol sources and boundary-layer dynamics.